ANALISA PENGUASAAN BAHASA INGGRIS CALON SDM KEPARIWISATAAN DALAM MENYONGSONG PARIWISATA BUDAYA - Kadek Wiramarta (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
With the focus of Bali tourism development which is directed to the cultural tourism, every aspired tourism industry worker needs  to have deep understanding on cultural tourism, the implementation of it. However, students capability in carrying this responsibility still needs to be studied. This research aimed at identifying the students knowledge about cultural tourism and their perception and opinion regarding the English for Cultural Tourism study. To achieve these goals, a descriptive quantitative study as well as document study were conducted. There were a questionnaire handed out to 50 aspired tourism industry workers. Additionally, some documents were analyzed to achieve this goal. From this research it was found out that although many aspired tourism industry workers have confidence in their knowledge about cultural tourism, only a few students were confident enough to use English in explaining the culture to the tourist. Therefore, education institution which handle the development of human resources in tourism needs to give more focus on English for local culture. Keywords : English, Cultural Tourism